Pengembangan Sistem Pengelolaan Praktik Kerja Industri pada Sekolah Menengah Kejuruan (Studi Kasus : SMK PGRI 3 Malang) - Dedin Anike Putra; Achmad Arwan; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PRAKERIN (Industrial Work Practice) is a method to improve vocational high school (VHS) student skills before entering real world of working. SMK PGRI 3 Malang is one of the largest VHS in Malang City. PRAKERIN management in this school managed by Industrial Cooperation Division (BKI). There are four phases to manage PRAKERIN, those are placement, monitoring, judgment, and evaluation. At placement phase, it need a lot of time to plot a student in company. This is because student can't find a company independently, company needs always changing, and BKI have to re-record company needs manually. At monitoring phase, student don't have any back up data for their journal and PRAKERIN report still need a lot of time. At judgment phase, score recapitulation is still doing manually. The system development take case in SMK PGRI 3 Malang with placement, monitoring, and judgment as the boundaries. System development begin with requirements engineering till testing phase.. There are 80 functional requirements in requirements engineering phase. Laravel is used to implement the system. Unit test resulting 100% valid from 17 test cases and validation test resulting 100% from 145 test cases. User acceptance testing show that system is approved by the users. For further research there are some suggestion. First, adding automatic placement feature using artificial intelligence algorithm, automatic document numbering, and sending notification through another media. In addition, adding some criteria in user acceptance testing will be good to assure the quality of software developed..